Mapping on slope seepage problem using Electrical Resistivity Imaging (ERI) - Z. A., M. Hazreek; Z., M. Nizam; M., Aziman; M. F., Md Dan; M. Z., N. Shaylinda; T. B., M. Faizal; M. A., N. Aishah; Ambak, K.; Rosli, S.; Rais, Y. (IOP Publishing, 2018)
The stability of slope may influenced by several factors such as its geomaterial properties, geometry and environmental factors. Problematic slope due to seepage phenomenon will influenced the slope strength thus promoting to its failure. In the past, slope seepage mapping suffer from several limitation due to cost, time and data coverage. Conventional engineering tools to detect or mapped the seepage on slope experienced those problems involving large and high elevation of slope design. As a result, this study introduced geophysical tools for slope seepage mapping based on electrical resistivity method. Two spread lines of electrical resistivity imaging were performed on the slope crest using ABEM SAS 4000 equipment. Data acquisition configuration was based on long and short arrangement, schlumberger array and 2.5 m of equal electrode spacing interval. Raw data obtained from data acquisition was analyzed using RES2DINV software. Both of the resistivity results show that the slope studied consists of three different anomalies representing top soil (200 – 1000 Ωm), perched water (10 – 100 Ωm) and hard/dry layer (> 200 Ωm). It was found that seepage problem on slope studied was derived from perched water zones with electrical resistivity value of 10 – 100 Ωm. Perched water zone has been detected at 6 m depth from the ground level with varying thickness at 5 m and over. Resistivity results have shown some good similarity output with reference to borehole data, geological map and site observation thus verified the resistivity results interpretation. Hence, this study has shown that the electrical resistivity imaging was applicable in slope seepage mapping which consider efficient in term of cost, time, data coverage and sustainability.